2018
DOI: 10.1177/1087054718815581
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ADHD Through the Multi-Informant Approach: The Contribution of the Conners’ 3 Scales

Abstract: Objective: Symptoms of ADHD need to be present in at least two different settings to suggest a diagnosis, so multi-informant assessment approaches are usually adopted. The Conners’ Rating Scales offer three versions, completed by parents (Conners 3-P), teachers (Conners 3-T), and youth (Conners 3-SR). Nonetheless, there is a lack of studies examining the psychometric properties of the Parent and Teacher versions and the relation between each version of the Conners 3 scales. Method: The present work examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The advantages of the Conners scales have been supported by both studies confirming the excellent psychometric properties of the scales (e.g. Arias Martínez, Arias González, & Gómez Sánchez, 2013; Christiansen et al, 2016; Conners, Sitarenios, Parker, & Epstein, 1998; Izzo, Donati, & Primi, 2018a, 2019; Morales-Hidalgo, Hernández-Martínez, Vera, Voltas, & Canals, 2017) and clinical studies. In fact, research has demonstrated the effectiveness of the Conners scales in distinguishing people with ADHD from those with no clinical diagnoses; moreover, the Conners scales have been found to have predictive validity for the development of behavioral problems in adolescence (e.g.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The advantages of the Conners scales have been supported by both studies confirming the excellent psychometric properties of the scales (e.g. Arias Martínez, Arias González, & Gómez Sánchez, 2013; Christiansen et al, 2016; Conners, Sitarenios, Parker, & Epstein, 1998; Izzo, Donati, & Primi, 2018a, 2019; Morales-Hidalgo, Hernández-Martínez, Vera, Voltas, & Canals, 2017) and clinical studies. In fact, research has demonstrated the effectiveness of the Conners scales in distinguishing people with ADHD from those with no clinical diagnoses; moreover, the Conners scales have been found to have predictive validity for the development of behavioral problems in adolescence (e.g.…”
mentioning
confidence: 64%
“…The psychometric properties of the full-length forms of the Conners 3 scales have been previously tested and confirmed in cultural contexts different from the original one (Christiansen et al, 2016; Izzo et al, 2018a, 2019). Differently, the psychometric properties of the short forms of the Conners 3 have not been tested by any other study but the original one—in both the English version and the Spanish version, which was validated for the Spanish-speaking population of the United States (Conners, 2008).…”
mentioning
confidence: 95%
“…School psychologists rely on teacher-report and parent-report rating scales to assess the social and emotional functioning of children who are referred for assessment of potential attention-deficit hyperactivity disorder (ADHD) and often add self-reports for adolescents (Allen & Hanchon, 2013; Pelham et al, 2005). Although commonly-used behavior rating scales such as the Conners Rating Scales (Conners, 2008) and the ASEBA (Achenbach & Rescorla, 2001) have strong psychometric properties, the correlations between self-, parent-, and teacher-reports are often modest (Achenbach, et al, 1987; Izzo et al, 2019). It is therefore important for school psychologists to gain an understanding of the potential biases inherent in the reports from these different sources.…”
mentioning
confidence: 99%
“…Los Reyes et al, 2015;Gizer et al, 2008;Hughes & Gullone, 2010;Hunsley & Mash, 2007;Izzo, Donati, & Primi, 2019), it should be desirable to develop a VGS-C form for parents in order to have the possibility to collect an hetero-evaluation of the children's video-gaming habits, thus having a more comprehensive assessment of the riskiness of this behavior for children.…”
Section: Resultsmentioning
confidence: 99%